La Investigación cualitativa en Administración: ciencia y técnica (Revista Electrónica Calidad en la Educación Superior, 2021)
This essay addresses qualitative research in Administration from its own essence, seeking to recognize some of its characteristics and conditions that may differentiate it from other fields of human knowledge of a scientific nature, in an effort to enhance skills of new researchers in this regard, but also add to those who already have a road traveled, providing an integrating or current vision on it. It follows then a common thread that encompasses science in general, reviewing the methods and techniques availables in the qualitative administrative field.
Keywords: Administration, social sciences, qualitative, méthods, information.